DECISION SUPPORT SYSTEM FOR SELECTING OUTSTANDING EMPLOYEES BASED ON THESIMPLE ADDITIVE WEIGHTING (SAW) METHOD AND ANALYTICAL HIERARCHY PROCESS (AHP) - Mochammad Imam Sulistyo; Moch Hafid T; Yusuf Muhyidin (RISTEC : Research in Information Systems and Technology, 2022)
Employees are the company's most important asset, without the role of employee’s activities cannot be realized. Employees are serious in determining the plans and goals that must be achieved. Therefore, PT. Unibless Indo Multi periodically selects the best employees to increase the spirit of performance and employee dedication to the company. The selection of employees will be done computerized, so it is necessary for a system when considering all the criteria that support to determine the best employees. To support the decision-making system, a decision-making method is needed. PT employees choose the methods used in the decision support system are SAW and AHP methods. The SAW method is often called the weighted summation method. At the same time, the Analytical Hierarchy Process is a decision-making process that finds the best solution by outlining complex problems into a more complex form. Based on the results processed in this study with the use of either SAW and AHP method in the first rank obtained by Taufik with the same weight which is 0,66.